Self-medication in patients with suspected COVID-19 in remote clinical follow-up in Lambayeque - Barba-Ocares, Rosaelvira (2022)
Background: Due to the pandemic, the Peruvian State decided to implement quarantine during a period of 2020 which caused changes in behavior, one of those: choosing to self-medicate. Therefore, the objective of this study is to describe the characteristics of self-medication in patients suspected of COVID-19 in Lambayeque during 2020. Materials and methods: cross-sectional analytical observational study in which a telephone survey was applied to 462 patients randomly selected volunteers. Subsequently, a descriptive analysis was performed and associations were searched. Results: the mean age was 42 years (minimun age = 18; maximun age = 90), more than half were women (58%), the majority had higher education (61.7%), they lived in the urban area of ​​Lambayeque (86, 6%) and 64.9% were affiliated with EsSalud. More than half (53.9%) self-medicated during the pandemic, ivermectin (35.7%; n = 218) was the most consumed. It was found that not clear (p <0.05) nor truthful (p = 0.001) the information on how to prevent the transmission of SARS-CoV-2, was associated with self-medication. Conclusions: The studied population used ivermectin to “prevent” COVID-19, they acquired this in pharmacies thanks to the information obtained from a doctor. It is also concluded that believing that the information on COVID-19 prevention provided by the Peruvian media is not clear or is not truthful is associated with a greater probability of self-medication.